Mediating Faiths : Religion and Socio-Cultural Change in the Twenty-First Century. - Bailey, Michael; Redden, Guy (Ashgate Gower, 2011)
Religion is living culture. It continues to play a role in shaping political ideologies, institutional practices, communities of interest, ways of life and social identities. Mediating Faiths brings together scholars working across a range of fields, including cultural studies, media, sociology, anthropology, cultural theory and religious studies, in order to facilitate greater understanding of recent transformations. Contributors illustrate how religion continues to be responsive to the very latest social and cultural developments in the environments in which it exists. They raise fundament.